2016
DOI: 10.1038/cdd.2016.124
|View full text |Cite|
|
Sign up to set email alerts
|

Strong antitumor synergy between DNA crosslinking and HSP90 inhibition causes massive premitotic DNA fragmentation in ovarian cancer cells

Abstract: All current regimens for treating ovarian cancer center around carboplatin as standard first line. The HSP90 inhibitor ganetespib is currently being assessed in advanced clinical oncology trials. Thus, we tested the combined effects of ganetespib and carboplatin on a panel of 15 human ovarian cancer lines. Strikingly, the two drugs strongly synergized in cytotoxicity in tumor cells lacking wild-type p53. Mechanistically, ganetespib and carboplatin in combination, but not individually, induced persistent DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
3
15
0
Order By: Relevance
“…Onalespib for example, has been found to sensitize malignant glioma cells to temozolomide. The HSP90 antagonist ganetespib, has recently been investigated for sensitizing effects in ovarian cancer and pancreatic cancer cells to chemotherapy 25 and radiochemotherapy 26 , respectively. The HSP90 antagonist NVP-AUY922 potentiated anti-cancer effects of a BCL-2 inhibitor in small cell lung cancer 27 and demonstrated synergy in combination with trastuzumab in breast cancer 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Onalespib for example, has been found to sensitize malignant glioma cells to temozolomide. The HSP90 antagonist ganetespib, has recently been investigated for sensitizing effects in ovarian cancer and pancreatic cancer cells to chemotherapy 25 and radiochemotherapy 26 , respectively. The HSP90 antagonist NVP-AUY922 potentiated anti-cancer effects of a BCL-2 inhibitor in small cell lung cancer 27 and demonstrated synergy in combination with trastuzumab in breast cancer 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In nearly all experiments, we observed that Ganetespib considerably potentiates cell killing by hyperthermia, in line with a recent study that reported enhancement of the effects of hyperthermia by 17-DMAG [ 47 , 48 ]. It is worth noting that prolonged administration of Ganetespib alone can also sensitize cancer cells to radiation and some chemotherapeutic drugs [ 49 51 ]. Second, the increased inhibition of HR (and, potentially, other DNA repair mechanisms) by hyperthermia and Ganetespib sensitizes cells to multiple DSB-inducing agents, indirectly increasing their cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In the research of Kramer et al, it was shown that by jointly inhibiting DNA repair and cell cycle control mechanisms, HSP90 inhibitor ganetespib blocked the degradation of FANCA and the imbalance of nuclease DNA2. On this basis, ganetespib enhanced the anti‐tumour efficacy of carboplatin, thereby triggering overall chromosomal destruction, abnormal mitosis and cell death in ovarian cancer cells 46 . It has been reported that heterozygous carriers of FA gene mutations will not cause FA phenotype, but may increase the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%